Large Oil Shocks and Economic Growth: Evidence from Saudi Arabia - Banafea, Waheed Abdulrahman; Ali, Abdelaziz Abdelmegid (International Journal of Energy Economics and Policy, 2022)
This paper aims to analyze the impact of large oil shocks on economic growth in Saudi Arabia, using a standard VAR model and a Markov-switching heteroscedastic regime, by using a quarterly data from 1981Q1 to 2019Q4. The results indicated that there were three large negative oil shocks, 1986Q1, 2008Q4, and 2014Q4, but there was only one large positive shock in 1990Q3. The impulse response and variance decomposition analysis show that both large negative and positive oil shocks have positive impacts on economic growth in Saudi Arabia, although only large negative shocks are statistically significant. Furthermore, large oil shocks only have a significant positive impact on economic growth comparing with normal oil shocks.